THE EFFECT OF CIPLUKAN EXTRACT (Physalis angulata L.) TO THE NUMBER OF FIBROBLASTS IN IMIQUIMOD INDUCES PSORIASIS MICE MODEL - Irse Priyaganda Bani Musa; Thianti Sylviningrum; Dody Novrial; Muhamad Salman Fareza (Mandala Of Health, 2021)
Imiquimod induces activation of Th17 cells and dendritic cells that play a role in psoriasis. Ciplukan extract ( Physalis angulata L.) contains steroid compounds, flavonoids, alkaloids, and saponins such as Physalin B, Physalin F, Physalin G which have anti-inflammatory activity in psoriasis pathophysiology. This research is an experimental research with post test only with control group design. Thirty five female mice were divided into 7 groups. Group A: negative control, group B: positive control, group C induced by imiquimod and given with ciplukan extract 400 mg/kg BW for 7 days, group D induced by imiquimod and given with ciplukan extract 800 mg/kg BW for 7 days, group E induced imiquimod and given with ciplukan extract 1,200 mg/kg BW for 7 days, group F induced by imiquimod and given with methotrexate 1 mg/kg BW for 7 days, and group G induced by imiquimod and given with a combination of ciplukan extract 1,200 mg/kgBW and methotrexate 1mg/kgBW for 7 days. 7 days. The number of fibroblast cells was counted on the fifteenth day by taken a sample of mouse skin and made histological preparations and then counted manually used a microscope. The mean number of fibroblast cells in groups A, B, C, D, E, F, and G were 21.6±2.3, respectively; 39.2±5.5; 30.6±1.3; 24.0±2.8; 24.8±2.9; 28,4±3,0;28,2±3,2 . The results of the test One Way ANOVA showed a value of p = 0.000 (p < 0.05), so that the results are significant. Keywords: ciplukan extract, fibroblast, methotrexate , Physalis angulata